General Labor Well-Being in Latin American Dentists during the COVID-19 Pandemic - Evaristo Chiyong, Teresa; Cuevas-González, Juan Carlos; Mattos Vela, Manuel Antonio; Agudelo Suarez, Andres A; Armas Vega, Ana del Carmen; Diaz Reisnner, Clarisse Virginia; Lopez Torres, Ana Cristina; Martinez Delgado, Cecilia Maria; Paz Betanco, Manuel Amed; Perez Flores, Maria Antonieta; Piovesan Suarez, Sylvia; Pistochini, Adriana; et al. (2022)
Abstract: This study aimed to determine the general labor well-being of Latin American dentists according to sociodemographic characteristics during the COVID-19 pandemic. A cross-sectional study was conducted in a final sample of 2214 participants from 11 countries. A validated online questionnaire on general work well-being was used (data collection period from 1 June to 10 July 2021), containing two dimensions: psychosocial well-being and collateral effects. The sociodemographic characteristics of the dentists and their perception of the economic impact of the pandemic were also recorded. A multivariate linear regression analysis was performed (hierarchical regression model) to evaluate the joint effect of the explanatory variables on labor well-being and the changes in the variance between each model. A score of psychosocial well-being of 233.6 + 40.2 and collateral effects of 45 + 20.1 was found. Psychosocial well-being was associated with sex, country of origin, academic training achieved, type of dental activity, and perceived impact during the pandemic (p < 0.05). Somatization was frequently manifested through back pain (88.2%) and muscular tensions (87.2%). Women, those who worked 41 or more hours and had between 1 to 15 years of professional experience presented azgreater collateral effect (p < 0.001). The impact of the COVID-19 pandemic a year and a half after it began on the labor well-being of Latin American dentists was evidenced with important interactions with social characteristics.